2022
DOI: 10.1002/mds.28938
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of External Anal SphincterEMGPatterns in Multiple System Atrophy

Abstract: Background It is debated whether external anal sphincter (EAS) electromyography can distinguish between multiple system atrophy (MSA) and Parkinson's disease (PD), whereas its usefulness for MSA prognosis is unknown. Objectives We explored the diagnostic and prognostic value and clinical correlations of EAS electromyography patterns in MSA. Methods We collected clinical data and EAS electromyography findings in 72 patients with MSA and 21 with PD. Results We identified four EAS patterns. The normal pattern was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…[ 19 ] The more serious the electromyography changes are, the more likely the diagnosis of MSA will be, and the worse the prognosis of patients will be. [ 20 ] In our study, there was no statistical difference in the course of disease among the three groups. According to the average duration of MUPs in EAS-EMG and US-EMG, MSA-P had the longest average duration of MUP, followed by PSP and PD, which was consistent with the results of previous studies.…”
Section: Discussioncontrasting
confidence: 50%
“…[ 19 ] The more serious the electromyography changes are, the more likely the diagnosis of MSA will be, and the worse the prognosis of patients will be. [ 20 ] In our study, there was no statistical difference in the course of disease among the three groups. According to the average duration of MUPs in EAS-EMG and US-EMG, MSA-P had the longest average duration of MUP, followed by PSP and PD, which was consistent with the results of previous studies.…”
Section: Discussioncontrasting
confidence: 50%
“…[ 16 ] Recently, Todisco et al . [ 17 ] has explored the prognostic significance of EAS- EMG alterations in MSA and its co-relation with prevalence of bowel/bladder symptoms and poor outcome. Many studies have found EAS-EMG easier and better tolerated by patients when compared to urethral sphincter (US)-EMG.…”
mentioning
confidence: 99%